Determinants of Credit Constrained Firms: Evidence from Central and Eastern Europe Region - Apostolos Thomadakis (Oesterreichische Nationalbank (OeNB), 2016)
Based on survey data covering 6,547 firms in 10 Central and Eastern European countries we examine the impact of the banking sector environment, as well as the institutional and regulatory environment, on credit constrained firms. We find that small and foreign-owned firms are less likely to demand credit compared to audited and innovative firms. On the other hand, small, medium, publicly listed, sole proprietorship and foreign-owned firms had a higher probability of being credit constrained in 2008-2009 than in 2012-2014. The banking sector's environment analysis reveals that firms operating in more concentrated banking markets are less likely to be credit constrained. However, higher capital requirements, increased levels of loan loss reserves and a higher presence of foreign banks have a negative impact on the availability of bank credit. The evaluation of the institutional and regulatory environment in which firms operate shows that credit information sharing is negatively correlated with access to credit. Furthermore, we show that banking sector contestability can mitigate this negative effect. Finally, we find that in a better credit information sharing environment, foreign banks are more likely to provide credit.
Keywords: E51; G21; F34; L10; 330; access to credit; credit constraints; credit demand; credit information sharing; Kreditrationierung; Kredit; Nachfrage; Informationsverbreitung; Institutionelle Infrastruktur; Panel; Osteuropa